Methacrylate Polymers With “Flipped External” Ester Groups: A Review - Kumar, Dhiraj; Bolskar, Robert D.; Mutreja, Isha; Jones, Robert S. (Frontiers in Dental Medicine, 2022)
Current resin composites have favorable handling and upon polymerization initial physical properties that allow for efficient material replacement of removed carious tooth structure. Dental resin composites have long-term durability limitations due to the hydrolysis of ester bonds within the methacrylate-based polymer matrix. This article outlines the importance of ester bonds positioned internal to the carbon–carbon double bond in current methacrylate monomers. Water and promiscuous salivary/bacterial esterase activity can initiate ester bond hydrolysis that can sever the polymer backbone throughout the material. Recent studies have custom synthesized, with the latest advances in modern organic chemical synthesis, a novel molecule named ethylene glycol bis (ethyl methacrylate) (EGEMA). EGEMA was designed to retain the reactive acrylate units. Upon intermolecular polymerization of vinyl groups, EGEMA ester groups are positioned outside the backbone of the polymer chain. This review highlights an investigation into the degradation resistance of EGEMA using buffer, esterase, and microbial storage assays. Material samples of EGEMA had superior final physical and mechanical properties than traditional ethylene glycol dimethacrylate (EGDMA) in all degradation assays. Integrating bioinformatics-based biodegradation predictions to the experimental results of storage media analyzed by LC/GC-MS revealed that hydrolysis of EGEMA generated small amounts of ethanol while preserving the strength-bearing polymer backbone. Prior studies support an investigation into additional custom-synthesized methacrylate polymers with “flipped external” ester groups. The long-term goal is to improve clinical durability compared to current methacrylates while retaining the inherent advantages of acrylic-based chemistry, which may ease the implementation of these novel methacrylates into clinical practice.